(untitled) (Contemporary Journal of Social Science Review, 2025)
Teacher commitment urges teachers to exert their maximum efforts for students’ academic achievement, enthusiastically to realize the dreams of students’ learning success. The role of teachers in teaching commitment and learning environment for students’ academic success cannot be underestimated. Teachers’ commitment and devotion help them to create a supportive learning environment, which undoubtedly influences students’ learning outcomes. This constructive relationship of teachers’ teaching commitment and students’ learning environment encourages students to put their maximum efforts to develop their capabilities to achieve academic requirements, and teachers to utilize their utmost potential to impart knowledge through efficient teaching. A supportive learning environment enhances teachers’ teaching commitment. In this way, students’ learning is supported by providing them a child-friendly environment where they are free to discuss, cooperate, learn, share, participate, and have an equal opportunity to interact with teachers and peers. The population of the study included all public sector secondary schools for males and females in Punjab province. The Data sample was gathered from 899 male and 946 female students of 48 randomly selected schools from the districts of Okara, Gujrat, and Bahwalpur. Pakistan. A multistage stratified random sampling technique was employed to collect data through a survey method. This study was ex post facto research in nature. Correlational quantitative research design was used to observe the relationship of existing variables of the study. The results indicated that teacher teaching commitment and students’ psychosocial learning environment are significantly correlated. Descriptive statistics, Pearson ‘r’ correlation and regression analysis was conducted to analyze data with the help of SPSS 26.